The mystery of happiness [videorecording (DVD)] - Burman, Daniel S.; Francella, Guillermo, 1955-; Estévez, Inés, 1964- ([Publisher not identified], 2014)
Santiago and Eugenio are best friends who run a thriving electronics store together. One day, Eugenio doesn't come to work, and Santiago delays telling anyone while trying to figure out why. Then Laura, Eugenio's wife, shows up to say that Eugenio has disappeared. Perplexed, the two embark on a journey to find him, only to discover that true happiness can sometimes mean losing everything.